Pristimerin mediated anticancer effects and sensitization of human skin cancer cells through modulation of MAPK signaling pathways - Maha Al-Tamimi (17280550) (2022)
Squamous cell carcinoma is a frequent skin cancer still demanding to understand the underlying mechanisms for better clinical outcomes. Pristimerin, a natural quinonemethide triterpenoid, has shown promising therapeutic outcome due to its anti-cancer activity and multi-targeting potential. We explored the underlying mechanisms of pristimerin-induced programmed cell death of primary (A431) and metastatic (A388) cutaneous squamous cell carcinoma (cSCC) cells. Our results show that pristimerin inhibits growth and proliferation of cSCC through JNK activation. Moreover, pristimerin causes cell cycle arrest and induces cell death via apoptosis and autophagy. Interestingly, use of apoptosis (z-VAD-FMK) and autophagy (3-methyladenine) inhibitors confirmed vital role of programmed cell death in pristimerin-mediated anti-cancer actions. JNK inhibitor, SP600125, also mitigated pristimerin-induced apoptotic and autophagic actions. Moreover, pristimerin-mediated anti-cancer activity acts by generating reactive oxygen species (ROS) thereby inducing JNK signaling. Use of N-acetyl cystine (NAC), a universal ROS scavenger, significantly reversed pristimerin-induced programmed cell death through downregulation of JNK. Pristimerin sensitized skin cancer cells to conventional anticancer drugs cisplatin, azacytidine and doxorubicin through JNK activation, as confirmed by SP600125. Our results indicate that pristimerin mediates programmed cell death and sensitized skin cancer cells to conventional anti-cancer drugs via ROS-mediated JNK activation. Other Information Published in: Biomedicine & Pharmacotherapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biopha.2022.113950